EFEKTIVITAS BIMBINGAN KELOMPOK DALAM MENINGKATKAN KECERDASAN EMOSI PESERTA DIDIK KELAS XI JURUSAN IPA DI SMA NEGERI 13 PADANG - Yaksa, Rully Andi (Bimbingan dan Konseling, 2014)
The background of this study is the pupils still can not control and manage well the emotion yet, such as anger, hate, revenge, piqued, sadness, depression and weeping. This study aims at discovering the effectiveness of group coaching in improving the pupilsâ emotion perspicacity. The methodology of the study is descriptive quantitative by implementing Quasi Experiment Design. The pupils of science at grade eleventh is the population in total number 152 pupils and the sample is about 20 by purposive random sampling technic then they are divided into two: 1) experiment group is 10 pupils, 2) control group is 10 pupils. Questionnare is used as instrument. The data is analyzed by using t-test correlation.Â The product indicates that 1) The different description of emotion perspicacity between experiment group and control group before treatment shows that there is no significant differences, 2) The different description of emotion perspicacity between experiment group and control group before and after treatment points out it has no significant differences, 3) The different description of emotion perspicacity between experiment group and control group before and after treatment pinpoints that it has significant differences, 4) The different description of emotion perspicacity between experiment group and control after treatment results that there is significant differences